Artificial anaerobic cell dormancy for tumor gaseous microenvironment regulation therapy. (April 2019) - Chen, Chen; Su, Weiwei; Liu, Yanyan; Zhang, Jiawen; Zuo, Changjing; Yao, Zhenwei; Bu, Wenbo
Abstract: Oxygen is known as an irreplaceable gas in the lives of most eukaryotic cells, yet researchers underestimate its importance, as in the case in many studies of tumors. The variable oxygen content of malignant solid tumors increases the difficulty of treatment. Thus, it could be reasonably inferred that the tumor oxygen microenvironment, if efficiently and completely regulated, could bring certain changes to existing therapies. Based on this speculation, an acid-responsive, oxygen-scavenging and anaerobic-sensitizing nanoparticle was designed to regulate the oxygen level of solid tumor by creating an artificial anaerobic environment in our study. The Mg2 Si core, which acted as a deoxygenating agent, was able to consume tumor oxygen and cause cell dormancy, while the incorporated hydrophobic tirapazamin (TPZ) helped to kill the now-dormant tumor cells. This simple and nontoxic nanoparticle achieved controllable factitious anaerobic circumstance in solid tumor for the first time, displaying the considerable potential and promising application of tumor gaseous microenvironment regulation therapy.